Analisis Kemampuan Komunikasi Matematis Siswa SMK pada Materi - Thiara Ayu Sheila; Alpha Galih Adirakasiwi (Universitas Batanghari Jambi, 2022)
Having mathematical communication skills is one way to achieve the objectives of learning mathematics. The reason why the discussion of mathematical communication becomes very important is because mathematics can be used as a language and learning mathematics is included in social activities. This article aims to analyze the mathematical communication skills of SMK students using descriptive research methods and qualitative approaches. The sample selected was 26 students from class XII TBSM 4 with the sampling technique applied was purposive sampling. The instrument used is a written test by paying attention to indicators of mathematical communication skills, interviews, and observation of research results. The data analysis technique applied is content analysis. The results of the research in this article are in the form of an analysis of students' mathematical abilities per item of the research instrument. Based on the results of the study, the average student score was 39.31. Guidelines for the achievement of mathematical communication skills were also given, with 3 students in the very good category, 6 students in the moderate category, 9 students in the poor category, and 8 students in the very poor category.